EGS P04 Transgastric drainage of oesophageal perforations: The largest case series. (7th December 2022) - Lunt, Adam; Ariyarathenam, Arun; Chan, David; Humphreys, Lee; Sanders, Grant; Wheatley, Tim; Berrisford, Richard
Abstract: Background: Oesophageal perforation is associated with a high morbidity and mortality. Multiple operative and non-operative management strategies have been described. We first described the novel technique of transgastric drainage of oesophageal injuries in 2008. This has since been adopted across other units in the UK and Ireland. The technique exteriorises the site of the perforation by establishing vacuum drainage of the lumen of the oesophagus, whilst maintaining luminal patency and thereby encouraging healing by secondary intention. We present our 10 year experience with the largest case series in the literature. Methods: A retrospective analysis was undertaken of all patients with oesophageal perforation treated with transgastric drainage, over the last 10 years, in our specialist unit. Transgastric drainage was performed using a 36 Fr Chest drain inserted through the stomach, into the oesophageal lumen above the proximal extent of the perforation. This was endoscopically performed with either laparoscopic or open guidance. Gastropexy was performed. Continuous suction of -10cm water was applied to the drain until no leak was noted. Mediastinal decontamination and drainage was performed as needed. Nutrition was provided by total parenteral nutrition or feeding jejunostomy. Results: 35 patients were treated with transgastric drain. 68% (n=24) were male. Median age was 67 (26–84). 60% (n=21) being spontaneous perforations and 31% (n=11) were iatrogenic. Inpatient and 30-day mortality was 14% (n=5). Among patients who survived, the median length to resolution of leak on imaging was 34.5 days (6–80). Median length of stay was 39.5 (16–84) days. Conclusions: Transgastric drainage can be successfully used to treat oesophageal perforations of varied lengths. The mortality rate of 14% compares favourably with other methods of management for oesophageal perforation.